Variation in the reference range limits of thyroid function tests and association with the prevalence of levothyroxine treatment. Issue 2 (8th February 2023) - Razvi, Salman; Jabbar, Avais; Addison, Caroline; Vernazza, Jonathan; Syed, Akheel; Soran, Handrean; Leng, Owain
Abstract: Many individuals with marginally abnormal thyroid function test (TFT) results may be treated and it is unknown if the limits of the thyrotropin (TSH) and free thyroxine (FT4) reference intervals reported alongside the laboratory results are associated with the prevalence of levothyroxine treatment. We obtained information regarding reported TFT reference intervals from UK National Health Service (NHS) laboratories and evaluated its relationship with the prevalence of levothyroxine treatment for corresponding health areas for 2014. The upper limit of serum TSH was significantly, linearly, independently, and negatively associated with prevalent levothyroxine treatment: −0.54% (95% CI, −0.68% to −0.40%). The lower limit of serum FT4 was significantly and independently associated with the prevalence of levothyroxine treatment in a non-linear (J-shaped) manner with an increase being noted from a FT4 level of ≈9.5 pmol/L onwards. We conclude that minor changes in the reference range limits for serum TSH and FT4 are associated with levothyroxine treatment.